The Potentials of the Neem Tree in Ghana - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
GTZ. 1998. 127 pp.Gesellschaft für Technische Zusammenarbeit (GTZ), Division 45, Rural Development Pesticide Service ProjectPO Box 5180, 65726 Eschborn, Germany.Fax: +49 6196 797 180Email: peter.foerster@gtz.deWebsite: www.gtz.de